Challenges of Contemporary Muslims - Lina Pusvisasari; Rahmah Fitriah; Rabiatul Adawiyah; Muhammad Nur Ilhami (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
This research focuses on how Islam compares between the time of the Prophet and today. These differences occur as a result of a shift in the understanding and practice of Islamic teachings along with developments over time. The challenges faced by the Prophet and his previous companions were physical attacks, whereas in  contemporary times there is no longer any war or conflict between humans. There is a saying that Western nations advanced because they abandoned their holy book, while Muslims regressed because they also abandoned their holy book (Al-Qur’an). This expression may be true when we see how poor Muslims are in various sectors of life, from education, economics, to the development of science and technology. Meanwhile, Western countries are so advanced and powerful that they dominate the world with all their military, economic, socio-political and cultural power which influences Muslims and other parts of the world. In contemporary times, Muslims are experiencing Ghazwul Fikr, namely a war of ideas or intellectual war. Ghazwul fikr is a transformation of conventional war.